Antimicrobial-resistant Gram-negative colonization in infants from a neonatal intensive care unit in Thailand. Issue 2 (October 2019) - Roberts, T.; Limmathurotsakul, D.; Turner, P.; Day, N.P.J.; Vandepitte, W.P.; Cooper, B.S.
Summary: Antimicrobial-resistant Gram-negative bacteria are a major cause of morbidity and mortality in hospitalized neonates in South and South-East Asia. This study aimed to determine the dynamics of colonization with antimicrobial-resistant Gram-negative bacteria amongst patients in a neonatal intensive care unit (NICU) in Thailand. From 97 enrolled patients, 52% were colonized by an extended-spectrum β-lactamase (ESBL) organism at some point during their stay and 64% were colonized by a carbapenem-resistant organism. Rapid acquisition of ESBL-positive and carbapenem-resistant organisms was found. Once colonized with an antibiotic-resistant organism, patients remained colonized for the remainder of their NICU stay.